Managing Organizations in the Creative Economy Organizational Behaviour for the Cultural Sector - Saintilan, Paul; Schreiber, David (Routledge, 2017)
The creative and cultural industries represent a growing and important sector in the global economy. Thriving in these industries is particularly tough and organizations face unique challenges in the digital age. This textbook provides a vivid initiation into the creative industries workplace. Managing Organizations in the Creative Economy is the first textbook of its kind, introducing organizational behaviour theories and applying them to the creative world. The text is underpinned by the latest research and theoretical insights into creative industries management and organisational behaviour, covering contemporary issues such as business decision-making, ethics, and sexuality. The authors bring theory to life through practical examples and cases provided by industry experts, supported by specially created companion videos featuring managerial responses to the cases. This unique textbook provides readers with an applied theoretical understanding of organizational behaviour that will be of particular benefit to those looking to work in the creative and cultural industries. Students on courses such as arts business, arts management, music business and even the broader study of the entertainment industries will find this to be a vital read.- Resumé vydavatel
Keywords: organizační chování; organizační změna; management změny; podnikový management; management; kreativní průmysl; kulturní průmysl; organizational behavior; organizational change; management of change; industrial management; creative industries; cultural industries; elektronické knihy; monografie; případové studie; electronic books; monographs; case studies